A novel homozygous MFN2 mutation associated with severe and atypical CMT2 phenotype. (May 2018) - Iapadre, Giulia; Morana, Giovanni; Vari, Maria Stella; Pinto, Francesca; Lanteri, Paola; Tessa, Alessandra; Santorelli, Filippo Maria; Striano, Pasquale; Verrotti, Alberto
Abstract: Background: Charcot-Marie-Tooth (CMT) neuropathies represent the most common forms of inherited polyneuropathies. CMT2A, the axonal form, accounts for about one third of all CMT cases. Variants in the MFN2 gene have been recognized to be a major cause of CMT2A. To date, more than 100 pathogenetic mutations in MFN2 have been identified, leading to different neurological clinical spectrum, varying from hereditary neuropathies to more severe clinical phenotypes. Pathogenic variants in MFN2 mainly act in a dominant manner, although in a few sporadic or familial cases, homozygous or compound heterozygous mutations have been reported. Results: We describe a child carrying a novel homozygous MFN2 mutation leading to an early-onset sensorimotor axonal neuropathy with an atypical and severe phenotype. Conclusion: The case highlights a very rare mechanism of inheritance for MFN2 mutations and expands the clinical and allelic variance of severe CMT2A phenotype. Moreover, it proposes the involvement of cerebellar peduncles observed at neuroimaging as a novel clue to suspect the diagnosis and address genetic testing. Highlights: CMT2A is the axonal form of CMT-related neuropathies. In addition to the classic phenotype, several cases with atypical and uncommon clinical findings have been described in patients affected by CMT2A neuropathies. Pathogenic variants in MFN2 are the main responsible for CMT2A and hereditary motor and sensory neuropathy VI (HMSN VI), which is an axonal CMT neuropathy with optic atrophy. Genotype-phenotype correlation cannot yet be drawn, since the same variant can be associated to varying ages of onset of the disease and can cause different clinical phenotypes. Most pathogenic variants in MFN2 are inherited in a dominant fashion, although homozygous or compound heterozygous mutations have been reported in a few cases. A careful evaluation of concomitant brain imaging findings and focused correlation with key clinical aspects would yield an appropriate and accurate differential diagnosis.